Canopy parameters for tree and shrub species compositions in differently intervened land uses of an urban park landscape - Ozturk, Melih; Agirtas, Lutfi; Öztürk, Melih (Pergamon-Elsevier Science Ltd, 2021)
Emirgan Park, which covers almost 43 ha hosting variable tree and shrub species, is situated near the Bosphorus at the European side of Istanbul, Turkey. Different tree and shrub species and, their compositions display different canopy parameter values dependent particularly upon their diversity and characteristics. Our study investigated some canopy parameters of the coniferous and deciduous trees, and shrubs within the 30 differently intervened land uses of the Emirgan Park landscape. Therefore, April, May, June LAI values and LT-GF percentages of 242 tree and shrub canopies were analysed using the hemispherical photographing and then image analysis techniques. In total, 726 hemispherical photographs were taken from these 242 different canopy points of the Emirgan Park. The result data were evaluated and discussed based on the land uses these canopies were in and on the ten different compositions their canopies were aggregated into. The highest mean value of LAI with 2.34 m(2) m(-2) were recorded for the relatively less intervened and pine dominating Picnic Site V, while the lowest LT and GF were recorded both for the Picnic Site V and Secondary Entrance, with respectively 19% and 10% in June. The second canopy composition which is dominated by the coniferous trees with relatively vast canopy, showed the mean highest LAI values with 1.24 m(2) m(-2), 1.60 m(2) m(-2) and 2.19 m(2) m(-2) for the consecutive three months respectively. Nevertheless, LT-GF percentages were also the lowest for this second composition, being 38-22%, 33-18%, 24-13% respectively along the same period. On the other hand, the level of constructional interventions and associated spacing between the canopies have led to the diminishment of LAI values and increment of LT-GF principally within the built land uses, which were confirmed by the pairwise comparisons (LSDs below 0.01) between the land uses. However, this negative situation occurred even though the land uses had diverse tree and shrub species compositions.
Keywords: Istanbul-Emirgan Park; Canopy Compositions; Leaf Area Index (Lai); Light Transmission (Lt); Gap Fraction (Gf); Land Uses